Talent Management: Development of a Model for Oil and Gas Industry in India - Bahuguna, P. C.; Kumari, P. (Prabandhan: Indian Journal of Management, 2010)
The advent of the era of globalisation and liberalisation accompanied by the information technology revolution has transformed the world around us. This has made possible the free flow of people, technology and goods across the globe, business activities are no more limited and confined to the geographical boundaries of the countries .Ulrich and Brockbank (2005) observe that there has been exponential growth in international movements of goods and services. The traditional jobs have become blurred. The economies across the globe are experiencing new order. Globalisation is putting multifaceted pressure on the organisations that compete for customers with high expectations for performance, quality, and low cost. But running a company is not as difficult as it is thought, provided the managers are able to identify the critical and significant business threats and decide how those risks and threats will be mitigated (Verwaayen, 2008). Like any other business, the oil and gas industry is also facing a whole lot of dynamic challenges. The energy industry, being the key driver of economic growth of any country, is experiencing a growing interest of people across the globe. As a result, it has become the most important news story throughout the world. Besides an ever growing demand for oil and gas globally, the exploration and production budgets are expanding. Concerns about issues such as energy pricing, security of energy supply, greenhouse-gas emissions and climate change are creating new challenges along with the opportunities. The recent global financial turmoil has added fuel to the situation. Economic slowdown has accelerated the need for efficiency and profitability. But high on the list are workforce related issues. Some of the issues that are among the most prominent challenges faced by the Indian oil and gas companies are: lack of qualified and trained (such as geophysicists, geoscientist, petroleum engineers etc) human capital, unavailability of talent for the entry level jobs and lack of awareness and unattractiveness of the industry.